A PROSPECTIVE OBSERVATIONAL STUDY ON MEDICATION USE PATTERN IN PATIENTS WITH RISK FACTORS OF CHRONIC KIDNEY DISEASE - ALI, AVEZ; KUMAR, PAWAN; ANSARI, JAVED AKHTAR; FATIMA, MEENAZ; IRRUM, FIRDOUS (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The current study was undertaken to review and assess the medication usage pattern in patients with chronic kidney disease (CKD). Methods: A 12-month prospective observational study was carried out at Shadan Teaching and General Hospital, Peerancheru (Hyderabad), involving 384 CKD patients considering the inclusion and exclusion criteria. Medication evaluation for optimization was done using the World Health Organization (WHO) core prescribing indicators. Data collected were entered using Microsoft Excel. Descriptive statistics such as mean, percentage, and standard deviation (SD) were used to present sociodemographic characteristics of the study participants. Results: Out of the total of 384 patients, 249 (65%) were male and 135 (35%) were female with a mean age of 58.28 (SD: 13.12). A total of 384 prescriptions were scrutinized with a total of 3634 drugs, out of which drugs acting on the cardiovascular system were the most prescribed drugs (36.37%). The average number of drugs per prescription was found to be 9.08 considering the total number of prescriptions. The percentage of drugs prescribed by generic name was 15.57%. The percentage of encounters with antibiotics was 25%, whereas the percentage of encounters with injections was 86%. The percentage of drugs prescribed from the Essential Drug List or Formulary was found to be 26.36%. Conclusion: Assessment of medication usage patterns using the WHO core indicators in CKD patients helps to reinforce the current hospital guidelines for the optimal usage of medications. The introduction of a clinical pharmacist along with a multidisciplinary team provides intensive care to the patients and helps to improve the clinical outcome.